(untitled) (Fiep Bulletin - online, 2019)
Introduction: Body image is the self-conception of the body formed by the individual, constituted by psychological,biological and social factors, being that the psychosocials have a distorted organization of the body image and contain greatervalue in the emotional and social development. Objectives: To understand how the notion of real and ideal body self-imageamong students is manifested, as well as to identify their level of satisfaction with their body. Methods: The present study ischaracterized by a qualitative research and presents the descriptive and analytical methods. The sample consisted of 88students, of both sexes, between the ages of 13 and 18 years. Kakeshita and Almeida (2009) evaluated the perception andsatisfaction of body image in adolescents aged 15 to 21 years (Kakeshita et al., 2009). The Figure shows the numberedsilhouettes from 1 to 11, according to the genre, with extremes of thinness to severe obesity. Results: According to the datapresented, we found that 22.72% were satisfied with their current body image, 45.45% were dissatisfied with leanness and31.83% were dissatisfied with being overweight. Conclusion: It was concluded that most students surveyed are dissatisfied withbody self-image. In both the male and female groups, dissatisfaction with thinness prevails, followed by dissatisfaction withoverweight.